1985
DOI: 10.1111/j.1474-8673.1985.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

EXCITATORY 5‐HYDROXYTRYPTAMINE RECEPTORS IN THE CAT URINARY BLADDER ARE OF THE M‐AND 5‐HT2‐TYPE

Abstract: In anaesthetized cats, a biphasic contraction of the urinary bladder, consisting of an initial spike followed by a longer-lasting contracture, was elicited by 5-hydroxytryptamine (5-HT) in doses of 3-30 micrograms/kg, i.a. Administration of MDL 72222 (30, 100 and 300 micrograms/kg, i.v.), which specifically antagonizes the M-type 5-HT receptors, selectively blocked the spike phase of the 5-HT response. Ketanserin (30, 100 and 300 micrograms/kg, i.v.), on the other hand, eliminated only the second phase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…15 Clinical studies have demonstrated that ketanserin significantly increases maximum and mean urinary flow rates and significantly decreases urethral pressure. 16 However, ketanserin partially blocks a 1 -adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…15 Clinical studies have demonstrated that ketanserin significantly increases maximum and mean urinary flow rates and significantly decreases urethral pressure. 16 However, ketanserin partially blocks a 1 -adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In the periphery, 5-HT is a potent vasoconstrictor in many vascular beds, but the constriction seems to involve two distinct receptor subtypes: contractions to 5-HT in the rabbit aorta, rat aorta, rat tail artery and dog femoral artery are mediated by 5-HT2-receptors at which ketanserin is a potent and competitive antagonist (Humphrey, 1984;Peroutka, 1984); contractions in the dog saphenous vein and human and dog basilar arteries are mediated by 5-HT1 or 5-HTI-like receptors (Peroutka, 1984;Feniuk et al, 1985). However, no selective antagonist is available for characterization of these 5-HT,-like receptors, and indeed the phrase 5-HT,-like has also been used to describe the 5-HT receptors mediating vasodilatation (Marwood & Stokes, 1984), tachycardia (Saxena et al, 1985) and inhibition of transmitter release (Fozard, 1984a).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro study has shown that 5-HT causes contractions of urinary bladder preparations from several mammals (5). In most species, activation of 5-HT 2 receptor has been reported to cause contractions due to direct stimulation of smooth muscle cells of cat (6,7) and human (8) urinary bladder. Activation of 5-HT 3 receptor causes neurogenic contractions mediated by stimulation of the receptor located on the excitatory neurons in the cat (7), mouse (9), guinea pig (10), rabbit (11,12), and human (13,14).…”
mentioning
confidence: 99%